In situ fabrication of highly crystalline CdS decorated Bi2S3 nanowires (nano-heterostructure) for visible light photocatalyst application - Panmand, Rajendra P.; Sethi, Yogesh A.; Deokar, Rajashree S.; Late, Dattatray J.; Gholap, Haribhau M.; Baeg, Jin-Ook; Kale, Bharat B. (RSC Advances, 2016)
In situ synthesis of the orthorhombic Bi2S3 nanowires decorated with hexagonal CdS nanoparticles (nano-heterostructure) has been demonstrated by a facile solvothermal method. The tiny 5-7 nm CdS spherical nanoparticles are decorated on the surfaces of 30-40 nm Bi2S3 nanowires, successfully. Structural, morphological and optical studies clearly show the existence of CdS on the nanowires. A possible sequential deposition growth mechanism is proposed on the basis of experimental results to reveal the formation of the nano heterostructure. The heterostructures have been used as a photocatalyst for hydrogen production as well as degradation of methylene blue under solar light. The maximum hydrogen evolution i.e. 4560 and 2340 mu mol h(-1) 0.5 g was obtained from H2S splitting and glycerol degradation for Bi2S3 NWs decorated with CdS nanoparticles (nano-heterostructure) which is higher than that of the Bi2S3 NWs (3000 and 1170 mu mol h(-1) 0.5 g, respectively). The enhanced photocatalytical hydrogen evolution efficiency of the heterostructures is mainly attributed to its nanostructure. In the nano heterostructure, the CdS nanoparticles control the charge carrier transition, recombination, and separation, while the Bi2S3 nanowire serves as a support for the CdS nanoparticles. The photogenerated electron's migration is faster than the holes from the inside of a CdS nanoparticle to its surface or to the phase interface, resulting in a relatively higher hole density inside the CdS nanoparticle leaving electron density at surface of the Bi2S3 NWs. This influences the photocatalytic activity under solar light. Such nano-heterostructures may have potential in other photocatalytic reactions.